PENGARUH CURRENT RATIO (CR) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP HARGA SAHAM PADA PT HANJAYA MANDALA SAMPOERNA TBK PERIODE 2012 – 2023 - Adin Saputra; Hendri Prasetyo (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence  of Current Ratio (CR) and Total Assets Turnover (TATO) on the stock price of PT Hanjaya Mandala Sampoerna Tbk. for the 2012-2023 period. The method used in this study is quantitative descriptive with data collection techniques using secondary data. The population in this study consists of all Financial Statements of PT. Hanjaya Mandala Sampoerna Tbk and the samples in this study are financial position statements and income statements and the data analysis techniques used are descriptive statistical analysis, classical assumption tests, multiple linear regression tests, coefficient tests, and hypothesis tests through  the Statistical Product and Service Solution 26 (SPSS 26) program. The results of this study show that: Partially, the current ratio (CR) has an influence and significance on the stock price because t is calculated 7,221 > t table 2,228 and a significant value of 0,000 < 0,05. Partially, the total assets turnover had an effect and was significant on the Stock Price because the calculation was 3,854 > Table 2,228 and the significant value was 0,004 < 0,05. Simultaneously, the results of the F current ratio (CR) and total assets turnover (TATO) test have a significant influence on stock prices. This can be seen from  the value  of F-count > F-table or (32,238 > 4,256), this is also strengthened by a p value < sig. 0,50 or (0,000 < 0,050).